Expressão do biomarcador de células tronco (CK19) - análise de sobrevida geral e livre de doença em pacientes com carcinoma hepatocelular ressecados - Leonardo do Prado Lima (2022)
The expression of biomolecular stem cell markers in hepatocellular carcinoma (HCC) has been associated with poor prognosis and aggressive biological behavior. Tumors that express cytokeratin 19 (CK19), a stem cell biomarker, are considered aggressive, leading to lower overall and disease-free survival. The objective of this research was to verify the expression of CK19, through immunohistochemical analysis, in 87 patients (61 men and 26 women) who underwent resection of HCC with curative intent. All patients included in the study had preserved liver function. The immunohistochemical expression of CK19 was positive in 12 patients (15%), in which 9 (75%) EpCAM was positive. The mean alpha-fetoprotein values were 5637.77+/-30.53 (min.1.68; max.199,000.00) and the median was 13.97 (IQ: 4.2; IIIQ: 212). Virus C hepatitis was the main etiology of cirrhosis in patients (40.22%) followed by virus B (22.98%). HCC was present in 19 patients (21.84%) with non-cirrhotic liver and in 13 (14.94%) the etiology was ethanolic. Most patients underwent minor hepatectomy and the need for perioperative blood transfusion occurred in 32% of patients. The perioperative mortality was 12.64%. The mean length of hospital stay was 6.87 (min 3; max 33) days. Most CHCs were well differentiated. Angiolymphatic invasion was present in 44 (50.57%) of the tumors. There was no association between positive CK19 expression and the variables analyzed. Overall survival after resection of hepatocellular carcinoma was 83.4% in 12 months, 66.7% at 36 months and 44.3% at 60 months. Disease-free survival was 73.8% in 12 months, 37.8% at 36 months and 27.7% at 60 months. There was no positive association between CK19 expression and overall survival or disease-free survival. The number of nodules greater than 3 had a negative impact on the overall and disease-free survival curve (p=0.033 and p=0.004). In conclusion, the greater number of nodules had a negative impact on overall and disease-free survival, while CK19 positivity was not associated with patient survival.